Solid-phase synthesis of azaphthalocyanine-oligonucleotide conjugates and their evaluation as new dark quenchers of fluorescence - Kopecký, Kamil; Nováková, Veronika; Miletín, Miroslav; Kučera, Radim; Zimčík, Petr (Bioconjugate chemistry, 2010)
Hydrophobic nonaggregating metal-free azaphthalocyanines (AzaPc) of the tetrapyrazinoporphyrazine type were synthesized, characterized, and used for oligonucleotide labeling. Both 3'-end and 5'-end labeling methods using solid phase synthesis suitable for automatic processes in the DNA/RNA synthesizer were developed. The hydrophobic character of AzaPc enabled the anchoring of the conjugates on reverse phase of the oligonucleotide purification cartridge, thus enabling their simple purification. AzaPc did not show any fluorescence and extremely low singlet oxygen quantum yields (Φ(Δ) = 0.015-0.018 in DMF) in a monomeric state due to ultrafast intramolecular charge transfer. That is why they were investigated as a new dark quencher structural type. They profit particularly from absorption in a wide range of wavelengths (300-740 nm) that covers all fluorophores used in hybridization assays nowadays. As an example, quenching efficiency was evaluated in a simple hybridization assay using monolabeled probes. AzaPc-based probes efficiently quenched both fluorescein and Cy5 fluorescence by both resonance energy transfer and contact quenching. The results were compared with three established dark quenchers, and the AzaPc exerted better (BHQ-1 and BHQ-2) or comparable (BBQ-650) quenching efficiencies for both fluorophores.
Keywords: pyraziny; Oligonucleotides; Fluorescent Dyes; sekvence nukleotidů; Chromatography, High Pressure Liquid; Absorption; oligonukleotidové sondy; Pyrroles; absorpce; Oligonucleotide Probes; Spectrometry, Fluorescence; pyrroly; vysokoúčinná kapalinová chromatografie; oligonukleotidy; fluorescenční barviva; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Pyrazines; fluorescenční spektrometrie; Base Sequence